Synthesis of 1H-3-(2’-hydroxy-4-’methoxy)-5-substituted Phenyl-2-pyrazolines - Sonare, S.S.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
2´-Hydroxy-4´-methoxy-chalcones (1a–c) on condensation with hydrazine hydrate in ethanol gave 1H-3-(2´-hydroxy-4´-methoxy)-5-substituted phenyl-2-pyrazolines (2a–c). The reaction of (2a–c) with acetic acid gave the acetyl derivatives (3a–c) by direct and indirect method. Similarly reaction of (2a–c) with benzoyl chloride gave benzoyl derivatives (4a–c). The structures of the compounds have been supported by elemental and spectral data.